(untitled) (Religious dialogue and cooperation, 2026)
This paper explores the dual impact of globalization on Christianity. It argues that globalization may serve as the ideal vehicle for achieving Christianity’s ultimate goal of worldwide conversion through improved communication and travel, succeeding where past empires failed. Simultaneously, however, globalization presents an existential challenge to "modern imperial Christianity," characterized by its triumphalism and claims of superiority, by fostering a dynamic exchange of competing religions and worldviews. There are two main Christian responses to this shift: a smaller faction that violently resists globalization and a larger group that seeks to adapt and reform its theology for the new global reality. Ultimately, this paper suggests that globalization signals the end of imperial Christianity and necessitates a fundamental reformulation of what it means to be Christian in a global world.